IL-17A, IL-17F and IL-23 in patients with rheumatoid arthritis - Natalia A. Lapkina; Andrey A. Baranov; Olga P. Rechkina; Natalia E. Abaytova; Svetlana S. Zolotavkina; Alexander S. Artyuhov; Evgeny L. Nasonov (Научно-практическая ревматология)
The aim of the study was to determine the clinical and diagnostic value of interleukin (IL) 17A, IL-17F and IL-23 in rheumatoid arthritis (RA) patients in the advanced stage of the disease.Materials and methods. We examined 154 patients with a reliable diagnosis of RA according to ACR/EULAR (American College of Rheumatology/European Alliance of Associations for Rheumatology) criteria (2010), predominantly (73.4%) female, middle-aged (56.0 (50.0; 64.0) years), disease duration of 9.4 (3.0; 13.0) years, radiologic stages II (34.4%) and III (37.0%), and moderate to high activity (DAS28-ESR – 5.40 (4.65; 6.00). 83.8% of patients were seropositive for IgM rheumatoid factor (IgM RF) and 68.8% had antibodies to cyclic citrullinated peptide (ACCP). 144 (93.5%) patients were taking DMARDs (methotrexate, leflunamide, sulfasalazine) as well as nonsteroidal antiinflammatory drugs (NSAIDs) and glucocorticoids (GCs) up to 10 mg/day in terms of prednisolone.The serum levels of IL-17A, IL-17F and IL-23 were investigated using multiplex xMAR technology. The upper limit of norm (M+3σ) in 20 sera of healthy donors was 1.78 pg/mL for IL-17A, 9.5 pg/mL for IL-17F and 91.55 pg/mL for IL-23.Results. IL-17A (1.16 (0.50; 2.39) pg/mL) and IL-17F (5.02 (1.00; 138.80) pg/mL) concentrations in RA patients were not significantly different from controls (0.78 (0.00; 1.65) and 4.02 (1.46; 7.31) pg/mL; p>0.05). In contrast, IL-23 levels were significantly higher in patients than in donors (21.36 (2.50; 4626.22) and 14.63 (0.00; 91.55) pg/mL; p<0.05).High values of IL-17F (71 patients – 46.1%) and IL-23 (66 patients – 42.9%) were significantly more frequently detected than IL-17A (46 patients – 29.9%; p=0.003 and p=0.02, respectively). Hyperproduction of IL-17A and IL-17F was simultaneously observed in 37 (24.0%) patients, and 32 (20.8%) patients had an increase in IL-17A, IL-17F and IL-23. Correlations between IL-17A and IL-17F concentration (r=0.44; p<0.05), IL-17A and IL-23 (r=0.40; p<0.05), IL-17F and IL-23 (r=0.94; p<0.05) were found.No statistically significant differences were observed between the concentration of IL-17A, IL-17F, IL-23 and the frequency of their elevation in RA patients positive or negative for IgM RF, as well as ACCP.When IL-17A level was elevated, CDAI (Clinical Disease Activity Index) and SDAI (Simplified Disease Activity Index) indices and IgM RF concentration were significantly higher than in the comparison group (p<0.05). In patients with IL-17F hyperproduction predominance of ESR and C-reactive protein values was revealed in comparison with normal values of this index (p<0,05). At the same time, IL-17A concentration correlated with SDAI (r=0,17; p<0,05), IgM RF values (r=0,19; p<0,05) and ACCP (r=0,19; p<0,05). When IL-23 values were high, the HR was significantly lower 28 (p<0.05), and the groups did not differ in other measures of disease activity, IgM RF and ACCP. No differences in clinical and laboratory indicators of RA activity were found between patients with simultaneous elevation of one, two or three cytokines and groups of patients with their normal concentrations.In RA patients in the advanced stage of the disease, IL-17F hyperproduction prevails over the frequency of IL-17A elevation. The concentration of IL-23 in serum is significantly higher in patients with RA compared to the control group, and its high values are found in 42.7% of patients. The combined hyperproduction of IL-17A and IL-17F; IL-17A, IL-17F and IL-23 does not increase the proinflammatory potential of each individual cytokine.